Wound contraction effects and antibacterial properties of Tualang honey on full-thickness burn wounds in rats in comparison to hydrofibre - Khoo Yan-Teng; Halim Ahmad; Singh Kirnpal-Kaur B; Mohamad Noor-Ayunie (BMC, 2010)
Abstract Background Full-thickness burn wounds require excision and skin grafting. Multiple surgical procedures are inevitable in managing moderate to severe full-thickness burns. Wound bed preparations prior to surgery are necessary in order to prevent wound infection and promote wound healing. Honey can be used to treat burn wounds. However, not all the honey is the same. This study aims to evaluate the wound contraction and antibacterial properties of locally-produced Tualang honey on managing full-thickness burn wounds in vivo. Methods Thirty-six female Sprague Dawley rats were randomly divided into three groups. Under anaesthesia, three full-thickness burn wounds were created on the dorsum of the rats. The full-thickness burn wounds were inoculated with a specific organism (104), namely Pseudomonas aeruginosa (n = 12), Klebsiella pneumoniae (n = 12), or Acinetobacter baumannii (n = 12). The three burn wounds were dressed with Tualang honey, hydrofibre and hydrofibre silver respectively. Swab samples were obtained every 3 days (day 3, 6, 9, 12, 15, 18 and 21) for quantitative and semi-quantitative microbiological analyses. Clinical assessments, including observations concerning the appearance and wound size, were measured at the same time. Results There was a rapid 32.26% reduction in wound size by day 6 (p = 0.008) in the Tualang honey-treated wounds, and 49.27% by day 15 (p = 0.005). The wounds remained smaller by day 18 (p < 0.032). Tualang honey-treated rats demonstrated a reduction in bacterial growth in Pseudomonas aeruginosa inoculated wounds (p = 0.005). However, hydrofibre silver and hydrofibre-treated wounds are superior to honey-treated wounds with Acinetobacter baumannii (p = 0.035). There was no statistical significant of antibacterial property in Klebsiella pneumonia inoculated wounds. Conclusions Tualang honey has better results with regards to its control of Pseudomonas aeruginosa and its wound contraction effects on full-thickness burn wound in vivo.